Crisis Leadership and Financial Resilience in MSMEs: Qualitative Insights from Banten, Indonesia - Chyrinne, Ervana (IJOSMAS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in sustaining economic resilience in emerging economies; however, their vulnerability to external shocks exposes significant financial fragility. While existing studies predominantly emphasize financial instruments and policy interventions, the role of leadership—particularly crisis leadership—in shaping financial resilience remains underexplored, especially from a qualitative perspective. This study aims to examine how crisis leadership is enacted by MSME leaders and how it influences financial resilience during periods of disruption. Employing a qualitative interpretive research design, this study draws on in-depth semi-structured interviews with 15 MSME owners and owner-managers operating across diverse sectors in Banten, Indonesia. Data were analyzed using thematic analysis to capture leadership cognition, behaviors, and financial decision-making processes during crisis situations. The findings reveal four interrelated dimensions of crisis leadership that significantly contribute to financial resilience: crisis awareness and sense-making, adaptive financial decision-making, relational and communicative leadership, and psychological resilience accompanied by moral commitment. MSME leaders relied heavily on experiential judgment, relational networks, and ethical considerations to manage liquidity constraints, restructure costs, and sustain stakeholder trust. Financial resilience emerged not merely as a function of resource availability, but as an outcome of leadership agency and adaptive capability in navigating uncertainty. This study contributes to the literature by positioning crisis leadership as a central explanatory mechanism within financial resilience frameworks for MSMEs in emerging economy contexts. Practically, the findings highlight the need for leadership-focused capacity-building initiatives alongside financial support programs to enhance MSME sustainability during crises.